If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(-4y + 1) + -4y = 6(y + -2) + -7 Reorder the terms: -7(1 + -4y) + -4y = 6(y + -2) + -7 (1 * -7 + -4y * -7) + -4y = 6(y + -2) + -7 (-7 + 28y) + -4y = 6(y + -2) + -7 Combine like terms: 28y + -4y = 24y -7 + 24y = 6(y + -2) + -7 Reorder the terms: -7 + 24y = 6(-2 + y) + -7 -7 + 24y = (-2 * 6 + y * 6) + -7 -7 + 24y = (-12 + 6y) + -7 Reorder the terms: -7 + 24y = -12 + -7 + 6y Combine like terms: -12 + -7 = -19 -7 + 24y = -19 + 6y Solving -7 + 24y = -19 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -7 + 24y + -6y = -19 + 6y + -6y Combine like terms: 24y + -6y = 18y -7 + 18y = -19 + 6y + -6y Combine like terms: 6y + -6y = 0 -7 + 18y = -19 + 0 -7 + 18y = -19 Add '7' to each side of the equation. -7 + 7 + 18y = -19 + 7 Combine like terms: -7 + 7 = 0 0 + 18y = -19 + 7 18y = -19 + 7 Combine like terms: -19 + 7 = -12 18y = -12 Divide each side by '18'. y = -0.6666666667 Simplifying y = -0.6666666667
| 9x^2+27x-10=0 | | 3x+2(x-7)=2(x+4)-5 | | -16=b-19 | | 14y-5=25-y | | -1/9x=-2 | | 2cos^2(x)=2sin^2(x)-1 | | 4x^2-28+33=0 | | 16z^2+62=64z | | 7.2/1.2 | | 14a=3a+30+a | | 8x-(4x-9)=1 | | 3x^2-25-18=0 | | 42-4.5= | | 24x+4x^2=3 | | 2x^4+3x^3=x | | 5x-(2x-3)=15 | | 2x^2+3x^3=x | | 6x+x^2=3 | | x+.08x=162 | | 21=6x-4x | | 24x10=21/2 | | (36-2x)/18 | | (7x-3)+x+(x-4)=646 | | 36-2x/18 | | 3x+6=105 | | 7/15x2/3 | | 7a+5b=-58 | | -8x+6(x-3)=-36 | | 5x+x+2=9x-14 | | 6(4x-3)+12X+10(x-4)=646 | | 4+2w=-10 | | .012n+0.07(4500-n)=0.08(4500) |